2004
DOI: 10.1086/422137
|View full text |Cite
|
Sign up to set email alerts
|

The Gas‐Phase Formation of Methyl Formate in Hot Molecular Cores

Abstract: Methyl formate, HCOOCH 3 , is a well-known interstellar molecule prominent in the spectra of hot molecular cores. The current view of its formation is that it occurs in the gas phase from precursor methanol, which is synthesized on the surfaces of grain mantles during a previous colder era and evaporates while temperatures increase during the process of high-mass star formation. The specific reaction sequence thought to form methyl formate, the ion-molecule reaction between protonated methanol and formaldehyde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
151
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(156 citation statements)
references
References 38 publications
(44 reference statements)
3
151
0
1
Order By: Relevance
“…Most of the more complex species predicted to be abundant by the Charnley et al (1995) model remain undetected, although one of these (not expected to be the most abundant one), ethyl formate HCOOC 2 H 5 , has recently been detected in Sgr B2 (Belloche et al 2009). This ice mantle methanol release/gas-phase post-processing model could not produce enough methyl formate when calculations by Horn et al (2004) showed that the reaction CH 3 OH + 2 + H 2 CO was not possible at interstellar temperatures.…”
Section: Dimethyl Ether and Methyl Formate Observations In Other Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the more complex species predicted to be abundant by the Charnley et al (1995) model remain undetected, although one of these (not expected to be the most abundant one), ethyl formate HCOOC 2 H 5 , has recently been detected in Sgr B2 (Belloche et al 2009). This ice mantle methanol release/gas-phase post-processing model could not produce enough methyl formate when calculations by Horn et al (2004) showed that the reaction CH 3 OH + 2 + H 2 CO was not possible at interstellar temperatures.…”
Section: Dimethyl Ether and Methyl Formate Observations In Other Regionsmentioning
confidence: 99%
“…Because the main problem to form HCOOCH 3 from CH 2 OH + 2 and H 2 CO is an energy barrier, could this obstacle be removed if one considers that the ions are strongly accelerated with respect to neutrals at some places of an MHD shock? A few km s −1 would represent enough kinetic energy to overcome the reaction barrier, which is 128 kJ/mol (15 000 K or 1.2 eV) according to Horn et al (2004). New quantum calculations and/or laboratory work are required to test this hypothesis.…”
Section: How Do These Models Confront Our Orion Dimethyl Ether and Mementioning
confidence: 99%
“…Until a few years ago it was thought that methyl formate could be formed in the gas phase after the sublimation of icy mantles containing H 2 CO and CH 3 OH. Horn and colleagues studied the specific sequence of reactions that was supposed to lead to the synthesis of methyl formate (Horn et al 2004). The results of their theoretical and experimental gas-phase study have conclusively shown that the processes in the gas phase are unable to produce sufficient amounts of methyl formate.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been detected in low-mass star-forming regions (hot corinos), such as NGC1333-IRAS4B and IRAS 2A (Bottinelli et al 2004(Bottinelli et al , 2007. Its large abundance is difficult to account are only available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsweb.u-strasbg.fr/cgi-bin/qcat?J/A+A/500/1109 for with a production mechanism based only on gas phase reactions with methanol (Horn et al 2004) and grain chemistry should be involved in methyl formate formation. In 1959 Curl studied the chemical structure and the microwave spectrum of the parent methyl formate and 8 other isotopologues (Curl 1959).…”
Section: Introductionmentioning
confidence: 99%